Identifikasi Karakter Morfologi dan Reproduksi pada Thallophyta dan Bryophyta di UIN Sunan Gunung Djati Bandung - Amelia Alpha Benita; Anita Fitriani; Fajar Ramadhan; Fina Riyandita Masfurin; Gheisya Geiziana Grandisningtias; Ita Fitriyyah (Tumbuhan : Publikasi Ilmu Sosiologi Pertanian Dan Ilmu Kehutanan, 2024)
This study aims to identify morphological and reproductive characters in Thallophyta and Bryophyta in UIN Sunan Gunung Djati Bandung. Bryophytes have high species diversity and are known as the second largest group of plants after flowering plants. They play an important role in maintaining ecosystems, especially water balance and nutrient cycles, and serve as bioindicators due to their sensitivity to environmental changes. The study was conducted by taking samples of leaf lichens and crustose lichens on various substrates such as rocks, soil, and trees, then observed using a stereo microscope and binocular microscope. The results showed that Thallophyta, such as crustose lichens, have unique morphological structures and can reproduce through ascospores, while Bryophyta, such as leaf mosses, have a life cycle that includes gametophyte and sporophyte stages. Reproduction in leaf mosses occurs sexually through the antheridium and archegonium, and asexually through stolon fragmentation. In addition to their ecological role, lichens also provide important habitat for a variety of organisms and help maintain the balance of tropical forest ecosystems. The adaptation of lichens to a wide range of environmental conditions allows them to survive in various substrates and extreme situations. This study provides new insights into the role of lichens in ecosystems and their potential applications for environmental conservation and restoration. The results of this study can serve as a basis for biodiversity conservation efforts and sustainable environmental management. Therefore, it is important to take appropriate conservation measures to preserve the vital role of lichens in ecosystems and the overall health of the environment.